2021
DOI: 10.1007/s11356-021-15468-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomic profiling in workers with noise-induced hearing loss: a pilot study

Abstract: Noise-induced hearing loss (NIHL) remains a leading occupational related disease and is a serious public health problem. Hence, the identi cation of potential biomarkers for NIHL prevention and diagnosis has become an urgent work. To discover potential metabolic biomarkers of NIHL, plasma metabolomics analysis among 62 NIHL patients and 62 controls was performed using ultrahigh performance liquid chromatography-mass spectrometry (UPLC/MS).Orthogonal partial least square-discriminant analysis (OPLS-DA) model wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…Blood plasma was collected in three studies to investigate cisplatin-induced changes at the systemic level [ 20 ], the metabolomic blood profile in a patient with hearing loss due to mitochondrial mutation [ 21 ], and changes in the metabolomic analysis of plasma following noise exposure in humans [ 22 ]. The volumes used for analysis were larger but required collection in a heparinized tube followed by centrifugation before freezing [ 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood plasma was collected in three studies to investigate cisplatin-induced changes at the systemic level [ 20 ], the metabolomic blood profile in a patient with hearing loss due to mitochondrial mutation [ 21 ], and changes in the metabolomic analysis of plasma following noise exposure in humans [ 22 ]. The volumes used for analysis were larger but required collection in a heparinized tube followed by centrifugation before freezing [ 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The analytical methods used to perform the metabolomic analyses were NMR spectrometry in one study [ 7 ], GCMS in four studies [ 16 , 23 , 24 , 25 ], and LCMS in eight studies [ 15 , 17 , 18 , 19 , 20 , 21 , 22 ]. Mass spectrometry (GCMS and LCMS) has a greater sensitivity than NMR spectrometry; however, this technique suffers from limited reproducibility [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis revealed that DEPs involving in the significant signaling pathways consisted of some proteins (ITGA1, KNG1, CFI, FGF1, AKT2, and ATG5) closely related to autophagy and inflammatory response. Our recent studies indicated that autophagy and inflammatory response may be a key pathological mechanism involving in NIHL [ 15 ]. Thus, these six DEPs were selected for validation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this current study, we found that a set of DEPs related to autophagy and inflammation including three upregulated DEPs (ITGA1, KNG1 and CFI) and three downregulated DEPs (FGF1, AKT2, and ATG5) were involved in the PI3K/AKT pathway, ECM-receptor interaction, and focal adhesion pathway signaling pathways and may be important biomarkers of NIHL. Our previous studies reported that autophagy and inflammation may be noticeable pathological mechanisms involved in the risk of NIHL [ 15 , 32 ]. Western blotting suggested that the expression levels of FGF1, AKT2, and ATG5 were decreased, but the ITGA1, KNG1 and CFI expression levels were upregulated in noise-exposed mice, compared to control mice.…”
Section: Discussionmentioning
confidence: 99%